Deletion of protein tyrosine phosphatase 1b in proopiomelanocortin neurons reduces neurogenic control of blood pressure and protects mice from leptin- and sympatho-mediated hypertension. (December 2015) - Bruder-Nascimento, Thiago; Butler, Benjamin R.; Herren, David J.; Brands, Michael W.; Bence, Kendra K.; Belin de Chantemèle, Eric J.
Graphical abstract: Abstract: Protein tyrosine phosphatase 1b (Ptp1b), which represses leptin signaling, is a promising therapeutic target for obesity. Genome wide deletion of Ptp1b, increases leptin sensitivity, protects mice from obesity and diabetes, but alters cardiovascular function by increasing blood pressure (BP). Leptin-control of metabolism is centrally mediated and involves proopiomelanocortin (POMC) neurons. Whether these neurons contribute to leptin-mediated increases in BP remain unclear. We hypothesized that increasing leptin signaling in POMC neurons with Ptp1b deletion will sensitize the cardiovascular system to leptin and enhance neurogenic control of BP. We analyzed the cardiovascular phenotype of Ptp1b+/+ and POMC - Ptp1b−/− mice, at baseline and after 7 days of leptin infusion or sympatho-activation with phenylephrine. POMCPtp1b deletion did not alter baseline cardiovascular hemodynamics (BP, heart rate) but reduced BP response to ganglionic blockade and plasma catecholamine levels that suggests a decreased neurogenic control of BP. In contrast, POMC - Ptp1b deletion increased vascular adrenergic reactivity and aortic α-adrenergic receptors expression. Chronic leptin treatment reduced vascular adrenergic reactivity and blunted diastolic and mean BP increases in POMC - Ptp1b−/− mice only. Similarly POMC - Ptp1b−/− mice exhibited a blunted increased in diastolic and mean BP accompanied by a gradual reduction in adrenergic reactivity in response to chronic vascular sympatho-activation with phenylephrine. Together these data rule out our hypothesis but suggest that deletion of Ptp1b in POMC neurons protects from leptin- and sympatho-mediated increases in BP. Vascular adrenergic desensitization appears as a protective mechanism against hypertension, and POMC-Ptp1b as a key therapeutic target for the treatment of metabolic and cardiovascular dysfunctions associated with obesity.